Factors associated with newly diagnoses HIV-positive among antenatal mothers in prevention of mother to child transmission (PMTCT) program in Kelantan - Kamdi, Mohd Khairul Anwar (2018)
Background: Vertical transmission is common and important mode of HIV transmission in children and without intervention, 30% to 45% will be infected with HIV from the mother during pregnancy, the delivery of the baby or breast feeding. Malaysia embarked on national PMTCT Program in 1998. It covers four strategies: a) primary prevention of HIV for PMTCT; b) preventing unintended pregnancies among HIV-positive women; c) preventing vertical transmission or HIV transmission from women to their infants; and d) providing care, treatment and support for mothers with HIV and their children. Safer modes of delivery which usually caesarean section are applied in these strategies and replacement feeding to baby born from HIV positive mothers will be supplied by MOH until the baby is 24 months old. Objective: This study aims to describe and determine associations of sociodemographic, obstetric history and risks of mothers and husband with newly diagnosed HIV-positive antenatal mothers in PMTCT program in Kelantan from 2009-2017.